(untitled) (Journal of Bangladesh Academy of Sciences, 2020)
The study explores the thermal-hydraulics parameters of a condenser of a nuclear power plant with 1200MWe net electric output and 37% thermal efficiency using empirical correlations of pressure drop and heat transfer coefficient both for the tube and shell sides. Considering a two-phase fluid system, a shell and tube condenser with coolant water on the tube side and condensing steam on the shell side has been selected. For designing a condenser with a thermal load of 2060MWth, the input temperature data of cold fluid inlet and outlet temperatures are taken as 29.4ºC and 40ºC while the condensation temperature is taken as 53.97oC. Transverse, two-pass condenser with 4 shell tanks has been considered in this study and the length of each shell tank is taken as 14m. Based on these input data, this work finds heat transfer area, logarithmic mean temperature difference (LMTD), and convection heat transfer coefficient inside the tubes as 549536m2, 18.74°C, and 2869.85W/m2.ºC respectively for 20mm tube outer diameter. Hydrodynamic parameters relating to the friction factors and pressure drops on tube side are found as 0.031 and 14.86kPa respectively. Similar design data have been generated for varying coolant inlet temperatures and tube inner diameters. Results reveal that velocity of flow inside the tubes as well as the number of tubes in a bundle decrease with the increase in tube diameter. Finally, the thermal-hydraulic data may be used to design a large scale commercial condenser to be applicable for a large scale nuclear plant since limited design data are available in the literature. Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 181-189, 2019